2022
DOI: 10.3389/fmicb.2022.1052420
|View full text |Cite
|
Sign up to set email alerts
|

In-process real-time probiotic phenotypic strain identity tracking: The use of Fourier transform infrared spectroscopy

Abstract: Probiotic bacteria, capable of conferring benefits to the host, can present challenges in design, development, scale-up, manufacturing, commercialization, and life cycle management. Strain identification is one of the main quality parameters; nevertheless, this task can be challenging since established methodologies can lack resolution at the strain level for some microorganisms and\or are labor-intensive and time-consuming. Fourier transform infrared spectroscopy (FTIRS) has been largely used for the investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The IR Biotyper ® is also applicable for food quality control to verify if the starter culture strains added during production remain consistent throughout the process. It has been employed to accurately differentiate four Lactiplantibacillus plantarum probiotic strains [ 44 ]. In this study, it demonstrated high discriminatory power even when the strains were cultivated under different conditions.…”
Section: Application Of Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The IR Biotyper ® is also applicable for food quality control to verify if the starter culture strains added during production remain consistent throughout the process. It has been employed to accurately differentiate four Lactiplantibacillus plantarum probiotic strains [ 44 ]. In this study, it demonstrated high discriminatory power even when the strains were cultivated under different conditions.…”
Section: Application Of Ftir Spectroscopymentioning
confidence: 99%
“…In this study, it demonstrated high discriminatory power even when the strains were cultivated under different conditions. Interestingly, the growth medium (broth and agar) did not affect its ability to distinguish the four probiotic strains [ 44 ]. In fact, broth cultures exhibited higher reproducibility and discriminatory power compared to agar cultures.…”
Section: Application Of Ftir Spectroscopymentioning
confidence: 99%
“…Notably, the IR Biotyper ® (IRBT) system (Bruker Daltonics, Bremen, Germany) based on FTIRS technology was launched in 2017 as a promising system in the field of microbial strain typing. Multiple successful applications have been reported [13] in the field of food, veterinary and water microbiology [14][15][16], as well as in hospital hygiene [17][18][19][20][21] and probiotic production [22,23].…”
Section: Introductionmentioning
confidence: 99%